Cytotoxic effects of pinnatane a extracted from Walsura pinnata (MELIACEAE) on liver cancer cells / Nurhisyam Zakaria - Nurhisyam , Zakaria (2019)
The main objective of the study is to identify the cytotoxic activity of pinnatane A, a glutinane type triterpene extracted from bark of Walsura pinnata (Meliaceae). MTT assay was used to analyse the selectivity of pinnatane A in inducing cell death in cancer and normal cells. Various assays were carried out to analyse the anti-cancer properties of pinnatane A, such as Live/Dead assay for microscopic visualization of cell death; cell cycle analysis using propidium iodide (PI) to identify the cell cycle arrest phase; annexin V- fluorescence isothiocyanate (FITC)/PI flow cytometry assay to measure percentage of cell populations at different stages of apoptosis and necrosis; and DNA fragmentation assay to verify the late stage of apoptosis. Preliminary MTT assay demonstrated dosedependent effects of pinnatane A against twelve cancer cell lines and one normal cell line. Pinnatane A was found to induce prominent time-dependent cytotoxicity in both liver cancer cell lines, Hep3B and HepG2 with minimal effects on normal cell line, MRC-5. Live/Dead assay visualized the disruption of cell integrity leading to cell death. Cell cycle analysis indicated cell arrest at G0/G1 phase, and annexin V-FITC/PI dual staining demonstrated that pinnatane A triggered apoptosis in Hep3B cells and necrosis in HepG2 cells. DNA fragmentation assay visualized DNA laddering in Hep3B cells while DNA smearing was observed in HepG2 cells to confirm the induction of apoptosis and necrosis in the respective cell lines. In conclusion, pinnatane A, a natural product from the Malaysian flora exhibited potential pharmaceutical use for cancer treatment.